ECONOMIC PRODUCTION QUANTITY MULTI PRODUK MESIN TUNGGAL DENGAN PROSES PENGOLAHAN ULANG - Hanif Hadi M; Siti Khabibah (Jurnal Matematika, 2012)
Efficiency production can be done by rework of the goods with imperfect quality of the resulting decrease in the production process, rework process itself can be done in one cycle and which is separated from the production cycle. With the model of Economic Production Quantity (EPQ) multi products single machine with rework process, will get the size of production and the optimal production time in the production activities are carried out using a multi products single machine and the presence of the reprocessing is done directly in the production cycle, so as to minimize costs. By analyzing the changes in calculation parameters of this model produces policies against the possibility that may occur during the production process.